ÐœÐ¾Ð´Ð¸Ñ„Ð¸ÐºÐ°Ñ†Ð¸Ñ Ð±ÐµÐ»ÐºÐ¾Ð² Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½Ð¾-Ñ†Ð¸Ñ‚Ð¾ÑÐºÐµÐ»ÐµÑ‚Ð½Ð¾Ð³Ð¾ ÐºÐ¾Ð¼Ð¿Ð»ÐµÐºÑÐ° Ð¿Ñ€Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ð¸ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð² Ð¿Ñ€Ð¸ÑÑƒÑ‚ÑÑ‚Ð²Ð¸Ð¸ ÐŸÐÐž-1500 - Zemlyanskikh, N. G.; Zubov, P. M.; Babiychuk, L. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
In the work there were investigated the modifications of protein content of membrane-cytoskeleton complex in erythrocytes exposed to PEG-1500 solution and cryopreserved under its protection in the media with different ionic strength and varying concentrations of bivalent ions. Peculiarities of erythrocyte protein spectra in membrane-cytoskeleton complex caused by PEG-1500 and low temperature were established.